Antimicrobial activity against periodontopathic bacteria, cell toxicity against gingival fibroblasts and antinflammatory effect of crude extract from mangosteen - Kitti Torrungruang; Suchada Chutimawarapun (Chulalongkorn University, 2008)
Extract from mangosteen pericarp has demonstrated various pharmacological activities including anti-bacterial, anti-inflammatory and anti-fungal. It may have potential for the treatment of periodontal disease, which is a chronic inflammatory disease caused by anaerobic bacteria. The aim of this study was 1) to investigate the toxicity of mangosteen extract to human gingival fibroblast, 2) to examine the anti-bacterial activity of the extract against periodontopathic bacteria including P. gingivalis and A. actinomycetemcomitans, and 3) to examine the inhibitory effect of the extract on PGE[subscript2]) production in lipopolysaccharide (LPS)-activated peripheral blood monocytes. The changes in cell viability were observed by inverted phase contrast microscopy and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenytetrazolium bromide (MTT) assay. The extract was not toxic when exposed to fibroblasts for up to 48 hours at the concentration of 200 [M]g/ml or less. The extract exhibited anti-bacterial activity against P. gingivalis, but not A. actinomycetemcomitans. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) against P. gingivalis were 20 and 40 [M]g/ml, respectively. The anti-inflammatory activity of the extract was determined by measuring PGE[subscript2] production with enzyme-linked immunosorbent assy (ELISA). The extract significantly inhibited LPS-induced PGE production in a dose-dependent manner. Its inhibitory effect reached maximal level at 10 [M]g/ml. These results suggest that the extract from mangosteen pericarp may be beneficial for periodontal treatment.